2005
DOI: 10.1002/sim.2211
|View full text |Cite
|
Sign up to set email alerts
|

Inference of nested variance components in a longitudinal myopia intervention trial

Abstract: This paper was motivated by a double-blind randomized clinical trial of myopia intervention. In addition to the primary goal of comparing treatment effects, we are concerned with the modelling of correlation that may come from two possible sources, one among the longitudinal observations and the other between measurements taken from both eyes per subject. The data are nested repeated measurements. We suggest three models for analysis. Each one expresses the correlation differently in various covariance structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In addition, 268 Asian and 201 white participants underwent separate analysis in the 1.0% atropine group for ethnic comparison. The study characteristics are listed in the Table . Low-dose atropine was investigated in 2 studies, 27,37 moderatedose atropine in 7 studies, 24,28,29,34,[36][37][38] and high-dose atropine in 13 studies, 17,[23][24][25][26][27][28][29][30][31][32][33]35 together resulting in 22 experimental groups in 19 studies. Ten studies were conducted in Taiwan, 3 in the United States, 3 in Singapore, 2 in Mainland China, and 1 in Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 268 Asian and 201 white participants underwent separate analysis in the 1.0% atropine group for ethnic comparison. The study characteristics are listed in the Table . Low-dose atropine was investigated in 2 studies, 27,37 moderatedose atropine in 7 studies, 24,28,29,34,[36][37][38] and high-dose atropine in 13 studies, 17,[23][24][25][26][27][28][29][30][31][32][33]35 together resulting in 22 experimental groups in 19 studies. Ten studies were conducted in Taiwan, 3 in the United States, 3 in Singapore, 2 in Mainland China, and 1 in Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…Of the atropine vs control group comparison, 1 study 39 reported data on low-dose atropine; 5 studies, 24,34,[36][37][38] on moderate-dose atropine; and 11 studies, 17,[23][24][25][26][27][30][31][32][33]35 on high-dose atropine. Seven RCTs 17,[23][24][25][26][27][28] (n = 1349) and 9 cohort studies [31][32][33][34][35][36][37][38][39] (n = 1308) reported data on refraction.…”
Section: Refractionmentioning
confidence: 99%
“…It has been demonstrated in Hsiao et al [14] that the correlation may be explained in the wrong direction if the data were fitted with an incorrect model structure. Indeed, the estimates of variance components of errors and random effects can be biased, and therefore one may reach an incorrect conclusion about the existence of random effects.…”
Section: Ebma and Computationmentioning
confidence: 96%
“…In addition, environmental covariates such as sex, age, indicator of education more than 12 years of schooling (Education), sighted distances for reading (Distance), and hours of "close-up work" (watching TV, doing computer work, reading books, writing, sewing, drawing and so on) at childhood (KCHR), at elementary school age (PCHR) and at senior high school age (SCHR), respectively, were recorded in the questionnaire. Because the covariates, sex, anterior chamber depth, axial length and astigmatism were important risk factors associated with myopia [12,14], we forced each model to include these four variables. The EBMA approach begins with all combinations of the other eight variables.…”
Section: Application Of a Twin Studymentioning
confidence: 99%
See 1 more Smart Citation